Predictors of Attendance and the Impact of Attendance on Outcomes for a Parenting Programme in Two Southeast Asian Countries - Janowski, Roselinde Katharina (Department of Psychology, 2021)
Background: Children living in low- and middle-income countries (LMICs) experience alarmingly high rates of maltreatment, frequently at the hands of caregivers. Group-based parenting programmes show promise for reducing and preventing child maltreatment, as well as for improving positive parenting, child behaviour problems, and caregiver mental health. However, parenting programmes can only benefit families if caregivers participate in them. Using secondary data, this study thus aimed to 1) identify factors that affect attendance and 2) investigate the impact of attendance on outcomes within two randomised controlled trials of Parenting for Lifelong Health (PLH) for Young Children for caregivers of children aged 2-9 years in Thailand (N = 120) and 2-6 years in the Philippines (N = 120). The interventions were delivered within existing service delivery systems in both countries, over eight weekly sessions (Thailand) or 12 sessions every second week (Philippines). Method: To address the first aim of this study, multivariable logistic regression models with robust sandwich estimators were used to examine family baseline characteristic as predictors of caregiver attendance in sessions. An exploratory approach was taken to test a range of factors that have previously been linked to attendance in parenting programmes, including economic and educational, social and health, parenting and child behaviour, and sociodemographic characteristics. To address the second aim, caregiver self-reports and observational assessments (Thailand only) from baseline, post-test, and follow-up were analysed using complier average causal effect (CACE) analyses to test the impact of attendance variability on the primary outcomes of child maltreatment, as well as secondary outcomes of positive parenting, dysfunctional parenting, child behaviour problems, and caregiver mental health. Results: Caregivers in Thailand attended 82.3% of sessions while those in the Philippines attended 61.8%. Overall, few baseline factors were significantly associated with attendance. In Thailand, caregivers who were less educated and those who were older were significantly more likely to attend sessions. In the Philippines, caregivers who were less healthy, those that who used more emotional abuse, and those who had boys rather than girls were significantly more likely to attend. Notably, caregivers who experienced higher rates of intimate partner violence significantly attended 8% fewer sessions in the Philippines. A comparison of CACE estimates to intention-to-treat estimates at post-test and at follow-up showed greater benefits of the intervention amongst caregivers who attended more sessions. Specifically, the strongest intervention effects were found for caregivers who attended at least 75% of the programme. Conclusion: This study showed no evidence that disadvantages related to lower socio-economic status were associated with attendance, suggesting that it is possible for vulnerable families in LMICs to attend parenting programmes. However, developing retention strategies that target subgroups who are at greater risk of missing sessions is especially important as higher attendance at sessions is positively related to greater improvements in caregiver and child outcomes.